PENGARUH KELOMPOK ACUAN DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN SKIN PROTECTOR MEREK BLINK - ATIKA W, TIARA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:Blink skin protector is a brand that is known and loved by consumers in Indonesia because of the quality of materials, price and design variations is given by the product brand. This study analyzes and discussesthe influence ofreference group anddesign producton purchase decisionBlink Skin Protector. The populations in this study were male consumersand women at least 18 years old who come and buy products Blink Skin Protector brand. Samples weretaken totaling 110 respondentsto the questionnaire data collection technique and the analyzedusing linear regression. This means that the effect of the independent variable is the reference group and product design together of the dependent variable that purchase decision, in which the variable reference group is the most dominant in influencing purchasing decisions. While the remaining is influenced by other variables. Keywords:purchasing decisions, reference group, product design.